The use of brabender plasticorder to study the fusion behaviour of calcium carbonate filled impact-modified PVC-U - Azman, Hassan; Yee, Joon Wee; Ko, Choon Ying; Ahmad Johari, Umat Lukman (2002)
The properties of poly(vinyl chloride) can be modified through the incorporation of suitable additives such as fillers. calcium carbonate is the most popular type of filler for PVC because of their excellent combination of low cost, high brightness and the ability to be used at high loadings. fusion has a profound influence on mechanical, physical and chemical properties. Due to these factors, various method assesment of fusion have been developed. In this project, rabender Plasticorder mixing chamber was used to study the fusion behaviour of calcium carbonate filled impact modified PVC-U was conducted. The other objective is to determine the effect of surface modification on the fusion properties. The result showed that the fusion time for the 0.8 micrometer particles size calcium carbonate filled impact-modified PVC-U had the shortest fusion time and highest torque. The fusion time increased with increasing calcium carbonate particle size. The coated calcium carbonate fillers increased the fusion time but decreased the melt viscosity compared to the uncoated calcium carbonate fillers. The use of the coupling agent increased the fusion time and increased the melt viscosity.